Penerapan Pencatatan Keuangan Berdasarkan Sak Emkm Pada Usaha Mikro, Kecil, Dan Menengah: Studi Rilly Bakery Kota Surabaya - Aditya Duta Aryansah (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research aims to determine the implementation of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) which are standards created and ratified directly by the IAI Council (Indonesian Accounting Association). The existence of SAK EMKM which is made simpler than SAK ETAP in preparing financial reports in accordance with specified standards can help companies to increase the trust of outside parties regarding financing as additional capital in their company. Judging from the type of data analysis, the research used in this writing is qualitative descriptive data. Qualitative research is an analysis method using data in the form of words, sentences, schemes and images. Rilly Bakery has not implemented the Financial Accounting Standards for Small and Medium Entities.